Akibat Hukum Terhadap Pihak Ketiga Atas Akta Perjanjian Perkawinan Dibawah Tangan Yang Disahkan Oleh Notaris Setelah Perceraian (Studi Putusan Pengadilan Tinggi DKI. Jakarta Nomor 477/PDT/2019/PT.DKI.) - Hauna Nur Azizah (Universitas Indonesia, 2020)
Which decided that the legalization of the marriage agreement does not apply toward a third party and must be ruled out, therefore the autor is interested in discuss the legal consequences of the third party involved and the validity of the marital assetthat is obtained during the marriage. To solve these problems, a normative juridical method with a typology of descriptive analytical was used. The data analysis was carried out using a statute approach and a case approach. The result of this research show that an under-hand marriage agreement made by legitimate parties and binds the parties with the condition of Section 29 subsection (1) of the Company Law, which allows it to be made under hand and provisions to be held after marriage can be justified based on the Constitutional Court Decision Number 69 / PUU-XII / 2015 dated 27 October 2016, where the marriage agreement is not interpreted as an agreement made before marriage (prenuptial agreement)but can also be made after the marriage takes place (postnuptial agreement).The judge in considering the decision and decides to make the Deed above which is made before a Notary to become “.. doesn’t have the value of evidentiary and must be ruled out”. The marriage agreement under-hand is considered not validated by a marriage registrar or a notary that is only valid internally (Husband-Wife) toward a third party may consider that as long as it has not been registered by a third party may consider that the marriage is took place with togetherness of marital assets. Keyword : Marriage agreement under-hand, legalization of Notary, and Third Party